2001
DOI: 10.1142/s0218810401000564
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Hand Tumours

Abstract: This paper presented clinical examples of some rare or uncommon presentations of tumours of the hand, including glomus tumour, intraosseous dermoid, fibrolipoma of the radial nerve, blastomycotic cyst and synovial sarcoma. Each lesion is illustrated by review of case histories, radiological and pathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…Recently, it has been shown that the occurrence of long-standing pain at the tumor site preceding the development of a bulge is significantly more common with synovial sarcomas than with other sarcomas [9]. The imaging appearance is nonspecific, and in all cases a biopsy is necessary to confirm the diagnosis [3,10,11]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that the occurrence of long-standing pain at the tumor site preceding the development of a bulge is significantly more common with synovial sarcomas than with other sarcomas [9]. The imaging appearance is nonspecific, and in all cases a biopsy is necessary to confirm the diagnosis [3,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the minimal acceptable margin has not been clearly established, and the surgeon must be aware of the possibility of microscopic infiltration of tumor cells into the pseudocapsule of the tumor [1,3,10]. Many investigators have suggested 1 cm to 2cm resection margins [1-3,10]. Because of proximity to the joints, the ablation can consist of either tenosynovectomy and/or post-operative radiotherapy and/or chemotherapy, or simply extremity segment amputation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitive 4,8,12 The incidence of tumor recurrence after surgery was reported as between 15% and 24% for glomus tumor of soft tissue origin. [13][14][15] Incomplete removal of intraosseous tumor also led to symptom recurrence and reoperation in 1 reported case. 10 Some authors 1,3,6,10 have suggested en bloc tumor excision, whereas others believed that amputation would be too radical for a benign digital lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Lipomas present as the most common tumor in the body [1]. The occurance of Lipomas in the hand is usually rare [3].…”
Section: Palmar Lipomatosis -A Rarest Clinical Presentationmentioning
confidence: 99%